Incidence of dengue fever and its clinical profile during an outbreak in a rural area in Tamil Nadu - Somasundaram, Deepak; Marimuthu, Somasundaram; Thiruselvam, Kavitha; Radhakrishnan, Shankar (Indian Journal of Child Health, 2019)
Background: In Southeast Asian countries, dengue is the major cause of pediatric morbidity and mortality and in that India reports the maximum number of cases. The annual incidence of dengue in India ranges from 8 to 33 million cases per year and an increased risk of dengue virus infection in children older than 5 years of age have been documented. Aim: The main objective of this study was to assess the incidence of dengue among the fever cases and to assess the clinical profile of various types of dengue fever and also to assess the predictive variables for the severity of dengue and their clinical outcomes. Methodology: A prospective longitudinal study was conducted at a pediatric hospital in a rural area of Tamil Nadu for a period of 6 months. A total of 325 patients were included in the study based on the study period and the inclusion criteria. For all the cases that were having a fever, basic blood investigations which includes hemoglobin, total count, and platelet count were performed along with peripheral smear study for malaria, dengue card test, and liver function test. Further, dengue positive patients were grouped into non-severe and severe dengue fever based on the operational definition formulated by the WHO. Results: The overall incidence of dengue among all the patients with fever was 71.3% among which 83.6% were non-severe dengue and the remaining 13.6% of the patients had severe dengue. Clinical signs such as palmar erythema, splenomegaly, and bleeding manifestations were more common in severe dengue patients than that of non-severe dengue, and this difference was found to be statistically significant. Hemoglobin and platelet count was found to be much lower among the patients with severe dengue along with raised liver enzymes (serum glutamic-oxaloacetic transaminase and serum glutamic pyruvic transaminase) than that of the non-severe dengue, and the difference was found to be statistically significant. Majority of the patients with severe dengue received crystalloid and few patients received blood products whereas only very few with non-severe dengue received crystalloids, and none of the patients in this group received blood products. Conclusion: Health-care personnel of all levels must be made aware of the clinical signs and symptoms of all dengue types. Early recognition, precise assessment and appropriate treatment with the help of the WHO revised classification and management guidelines would reduce the mortality due to dengue fever.